2022
DOI: 10.51253/pafmj.v72i3.4470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sofosbuvir and Daclatasvir in Achieving the End Treatment Response and Sustained Viral Response in Patients infected with Hepatitis C Virus Genotype 3

Abstract: Objective: To ascertain the efficacy of sofosbuvir combined with daclatasvir against hepatitis C genotype 3 infection. Study Design: Prospective longitudinal study. Place and Duration of Study: Ayub Teaching Hospital, Abbottabad, Pakistan, from Nov 2018 to Jan 2020. Methodology: About 262 patients were treated during the study. Patients with symptoms associated with liver failure, including ascites, uncontrolled bleeding, encephalopathy and other comorbidities, were excluded from the study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…A study conducted on 262 patients showed an ETR of 259 (98.9%) and sustained virological response in 248 (95.8%) patients when given a combination of sofosbuvir plus daclatasvir in genotype 3 patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted on 262 patients showed an ETR of 259 (98.9%) and sustained virological response in 248 (95.8%) patients when given a combination of sofosbuvir plus daclatasvir in genotype 3 patients [15].…”
Section: Discussionmentioning
confidence: 99%